KEDUDUKAN DAN AKIBAT HUKUM PENERAPAN PERMA NO.2 TAHUN 2012 - Fadliansyah Fadliansyah (JURNAL AKTA YUDISIA, 2020)
AbstrackThis research was made to know the position of PERMA NO.2 IN 2012 in the hierarchy of legislation and to know the PERMA's binding and enforceability. In this research using normative law research method with law approach, conceptual, and case approach. From this study found that the position of PERMA NO.2 IN 2012 in the hierarchy of legislation - legislation is under the law and the effect of the implementation of PERMA is null and void.Keywords: position, PERMA NO.2 IN 2012, Due to the law